Multi-parameter optimization of shell-and-tube heat exchanger with helical baffles based on entransy theory. (5th February 2018) - wen, Jian; Gu, Xin; Wang, Mengmeng; Liu, Yuce; Wang, Simin
Highlights: Entransy theory was firstly applied to study the heat performance of STHXsHB. The applicability of entransy theory on STHXsHB was firstly proved based on experimental data. The entransy dissipation thermal resistance is more sensitive to the helix angle. Three optimum configurations were obtained using the GA and entransy theory. Abstract: An optimization strategy combined the entransy theory and genetic algorithm was proposed in this paper. The applicability of entransy theory on shell-and-tube heat exchanger with helical baffles (STHXsHB) was firstly proved by the consistency of performance evaluation criteria (PEC) and entransy dissipation theory based on experimental data. The effects of helix angle, overlapped degree and shell-side velocity on thermal resistance (optimization objective) were discussed based on the minimum thermal resistance principle. The results showed that the entransy dissipation thermal resistance decreased with the shell-side velocity but increased with the helix angle. The overlapped degree nearly had no effect on the variation of entransy dissipation thermal resistance. According to the sensitivity study, the thermal resistance was considered to be mostly affected by the shell-side velocity and then the helix angle. Three optimum configurations were obtained by the genetic algorithm, for which the thermal resistance decreased by 7%. The combination of entransy theory and genetic algorithm can provide some theoretical guidance to optimize the configuration of shell-and-tube heat exchanger with helical baffles effectively.